Fabrication of vertically well-aligned NiSi2 nanoneedle arrays with enhanced field emission properties. (March 2021) - Huang, Y.H.; Lin, H.C.; Cheng, S.L.
Abstract: In this study, we demonstrated the controllable fabrication of periodic arrays of vertically well-aligned, fully-silicided NiSi2 nanoneedles with sharp nanotips on (100)Si substrates. The new approach proposed here eliminates the need for complicated and costly photolithographic processes and the use of toxic chemicals. All the produced vertical Si and NiSi2 nanoneedles were identified to be single crystalline and with the same geometric morphology and the same axial orientation of [100]. Additionally, the produced tapered NiSi2 nanoneedle array possessed excellent electron emission properties with a very low turn-on field of 0.85 V/μm, which is superior to many reported one-dimensional metal silicide nanostructures. Such an enhancement in the field emission can be attributed to the lower effective work function, sharp nanotips, single-crystalline structure, and good vertical alignment. The combination of the facile approach proposed here and superior electron emission performances make the well-ordered vertical NiSi2 nanoneedles promising candidates for vacuum nanoelectronics and field emission display applications. Highlights: A new approach was proposed to fabricate periodic NiSi2 nanoneedle arrays. The new method eliminates the need for complicated photolithographic processes. Fully-silicided NiSi2 nanoneedles had single-crystalline structure with axial direction [100]. Tapered NiSi2 nanoneedle array had superior electron emission properties with very low turn-on field of 0.85 V/μm. Has potential for making various tapered silicide-based field emission nanodevices.